2022
DOI: 10.1021/acsami.2c02080
|View full text |Cite
|
Sign up to set email alerts
|

Interlayer-Expanded MoS2 Nanoflowers Vertically Aligned on MXene@Dual-Phased TiO2 as High-Performance Anode for Sodium-Ion Batteries

Abstract: As a promising energy-storage and conversion anode material for high-power sodium-ion batteries operated at room temperature, the practical application of layered molybdenum disulfide (MoS2) is hindered by volumetric expansion during cycling. To address this issue, a rational design of MoS2 with enlarged lattice spacing aligned vertically on hierarchically porous Ti3C2T x MXene nanosheets with partially oxidized rutile and anatase dual-phased TiO2 (MoS2@MXene@D-TiO2) composites via one-step hydrothermal metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…To address the volume change, low electrical conductivity, and inevitable aggregation of MoS 2 anode in SIBs, Zhang and co‐workers designed a heterostructure of interlayer‐expanded MoS 2 nanoflowers vertically aligned on MXene@dual‐phase TiO 2 (MoS 2 @MXene@D‐TiO 2 ) (Figure 12f). [ 131 ] They first prepared Ti 3 C 2 T x MXene nanosheets by an acid (LiF + HCl) etching method. Then Na 2 MoO 4 ·2H 2 O, CH 3 CSNH 2 , and CTAB were dispersed in Ti 3 C 2 T x suspension.…”
Section: In Situ Growth Engineering On 2d Mxene For Rechargeable Batt...mentioning
confidence: 99%
See 1 more Smart Citation
“…To address the volume change, low electrical conductivity, and inevitable aggregation of MoS 2 anode in SIBs, Zhang and co‐workers designed a heterostructure of interlayer‐expanded MoS 2 nanoflowers vertically aligned on MXene@dual‐phase TiO 2 (MoS 2 @MXene@D‐TiO 2 ) (Figure 12f). [ 131 ] They first prepared Ti 3 C 2 T x MXene nanosheets by an acid (LiF + HCl) etching method. Then Na 2 MoO 4 ·2H 2 O, CH 3 CSNH 2 , and CTAB were dispersed in Ti 3 C 2 T x suspension.…”
Section: In Situ Growth Engineering On 2d Mxene For Rechargeable Batt...mentioning
confidence: 99%
“…f ) Schematic showing the fabrication process of MoS 2 @MXene@D-TiO 2 . Reproduced with permission [131]. Copyright 2022, American Chemical Society.…”
mentioning
confidence: 99%
“…Moreover, to integrate the intermittent renewables into the electric grid, the SIBs with high power and low cost are highly demanded 25 . In addition, the electrochemical performance of SIBs including capacity, efficiency, and energy/power density will deteriorate obviously when the temperature decreases/increases 26–28 . Accordingly, the wide‐temperature operation of SIBs is essential for satisfying the demand for practical applications in extreme weather and different regions (e.g., high‐altitude and tropical zones) 29,30 .…”
Section: Introductionmentioning
confidence: 99%
“…The as‐constructed MoS 2 @MXene@D‐TiO 2 heterostructure in sodium‐ion batteries delivers admirable high‐rate reversible capacity due to the built‐in electric field between the non‐homogeneous phases that promotes the high Na + transportation. [ 23 ] Meanwhile, Agresti et al suggested that the formation of heterojunctions between MXene and perovskite could regulate the arrangement of dipole moments. [ 24 ] Therefore, the construction of MXene heterojunction with perovskite is expected to improve both the arrangement of dipole moments and the utilization of polarized charges.…”
Section: Introductionmentioning
confidence: 99%